2009
DOI: 10.1111/j.1365-2966.2009.15308.x
|View full text |Cite
|
Sign up to set email alerts
|

S 235 B explained: an accreting Herbig Be star surrounded by reflection nebulosity

Abstract: The intent of this study is to determine the nature of the star and associated nebulosity S 235 B, which are located in a region of active star formation still heavily obscured by the parent molecular cloud. Low‐resolution (R= 400) long‐slit spectra of the star and nebulosity, and medium‐ (R= 1800) and high‐resolution (R= 60 000) spectra of the central star are presented along with the results of Fabry–Perot interferometric imaging of the entire region. Based on the long‐slit and Fabry–Perot observations, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Sh2‐235A Cluster is a compact H ii region of ≈20 arcsec (0.17 pc) in diameter (Felli et al 1997). For Boley et al (2009), the exciting star of Sh2‐235B Cluster is an early‐type Herbig Be star of spectral type B1V. Hodapp (1994) found a cluster in Sh2‐235B Cluster, which was confirmed by Wang, Testi & Felli (1997), Allen et al (2005) and Kirsanova et al (2008).…”
Section: Previous Studies On the G174+25 Stellar Contentmentioning
confidence: 64%
“…Sh2‐235A Cluster is a compact H ii region of ≈20 arcsec (0.17 pc) in diameter (Felli et al 1997). For Boley et al (2009), the exciting star of Sh2‐235B Cluster is an early‐type Herbig Be star of spectral type B1V. Hodapp (1994) found a cluster in Sh2‐235B Cluster, which was confirmed by Wang, Testi & Felli (1997), Allen et al (2005) and Kirsanova et al (2008).…”
Section: Previous Studies On the G174+25 Stellar Contentmentioning
confidence: 64%
“…We also found that source S235B is associated with Brα emission due to the presence of an H ii region. Recently, using spectroscopy, Boley et al (2009) reported that S235B is a source that belongs to a rare class of early‐type Herbig Be stars. SED modelling of source S235B (see Table C8) shows that it is an intermediate‐mass young star and our model results are consistent with the Boley et al (2009) results.…”
Section: Resultsmentioning
confidence: 99%
“…Krassner et al (1982) found recombination lines of hydrogen and the polycyclic aromatic hydrocarbon (PAH) emission features at 3.3, 8.7 and 11.3 μm associated with S235B. Boley et al (2009) attributed the central star of S235B to a rare class of early‐type Herbig Be star.…”
Section: Introductionmentioning
confidence: 99%
“…While most of these clumpy accretion diagnostics are observed in HAe stars, we can observe them also in few HBe stars (e.g. Boley et al 2009). Finkenzeller & Mundt (1984) have detected P Cygni profiles in the Hα and Mg ii h & k lines, in a large number of HAeBe stars.…”
Section: Accretion Diagnosticsmentioning
confidence: 96%